Pengaruh Motivasi Kerja dan Stress Kerja terhadap Kinerja Karyawan Jasa Pengiriman Online - Santoso, Iwan; Ignatius Andre Siboro (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
The challenge faced by companies in the field of human resources is to find ways to increase work motivation and alleviate the impact of work stress so that it can ultimately enable employees to achieve organizational goals. The purpose of this paper is to test the influence of work motivation and work stress on employee performance both partially and simultaneously. The analysis method used is quantitative verification analysis using the help of SmartPLS 4.0 software. The type of data used is primary data obtained through questionnaires filled out by 50 employees working in online delivery services. Data analysis has met the criteria for valid and reliable. Where the results of the study show that there is a positive and significant influence both partially and simultaneously between work motivation and work stress on the performance of online delivery service employees.